(untitled) (Research, Society and Development, 2021)
Thinking about an integrated curriculum is equivalent to think about combining enriching experience and knowledge throughout assisted pedagogical practice, collective planning, integrative projects creation, undergraduate and extension research as well as research projects and integrated professional practices. These are some of the groundbreaker practices used in order to achieve the goals set for one course. This integrative project concerns the development of a software that aims to manage a local food street market in Iporá, state of Goiás, by creating a mobile application that can ease the life of street market’s costumers by showing them the stands and its products along with their source and price, as well as improve the costumer-family farmers relationship. At first, a survey containing the food street markets that takes place in Iporá and the merchants’ profile was made, then the surveyed data were analyzed. And finally, the software was developed using Delphi computer language along with the database SQlite, and it was revealed that the application serves its purpose and is, by all means, according to the UX concepts.